CLINICAL IMMUNOBIOCHEMICAL MARKERS IN OPTIMIZING THE DIAGNOSTICS OF BRONCHIAL ASTHMA IN COMORBIDITY WITH TYPE 2 DIABETES MELLITUS - Faizullaeva N. Ya.; Mukhtorov Sh. M.; Raufov A. A. (Modern American Journals, 2025)
The relevance of the study is due to the high frequency of bronchial asthma (BA) and type 2 diabetes mellitus (T2DM), which mutually aggravate each other. The aim of the study was to investigate clinical and immunobiochemical markers to optimize the diagnosis and assess the severity of BA combined with T2DM.
Keywords: Bronchial asthma, type 2 diabetes mellitus, cytokines, endothelin-1, glycated hemoglobin, comorbidity, immunobiochemical markers.